Spectral Features and Stability of Oligomeric Pyranoanthocyanin-flavanol Pigments Isolated from Red Wines - Jingren He (2010)
The spectral characteristics and stability of three red wine pigments (pyranoMv-catechin, pyranoMv-epicatechin, and pyranoMv-dimer B3) toward pH variation and bisulfite bleaching, as well as their color stability and degradation during storage, have been studied. Unlike the absorbance spectra of most wine pigments, the intensity of which is more increased in more acidic conditions, oligomeric pyranoMv-flavanols have maximum absorbance at wine pH around 3.6, up to 30-50% higher than that in pH 1.0. This particular hyperchromic effect shown in mildly acidic solutions suggests the presence of intramolecular copigmentation in the molecule of pyranoanthocyanin-flavanols, giving rise to higher molar extinction coefficients around wine pH and contributing to the overall wine color. The most probable conformations were determined by computer-assisted model building and molecular mechanics. Besides exceptional stability toward pH variations, pyranoanthocyanin-flavanols were also shown to be entirely resistant to bleaching by sulfur dioxide. During a 6 month storage period, pyranoanthocyanin-flavanols were much more stable against degradation than the anthocyanin with the following order: pyranoMv-catechin > pyranoMv-dimer B3> pyranoMv-epicatechin > carboxy-pyranoMv >> Mv. Kinetic decomposition monitored by high-performance liquid chromatography-diode array detection-mass spectrometry revealed the formation of a new pigment (pyranone-Mv structure) and the cleavage of the interflavanic linkage of procyanidin dimer in the solutions containing carboxy-pyranoMv and pyranoMv-dimer B3, respectively. Despite some degree of decline of these oligomeric pyranoanthocyanins, their color intensity was surprisingly enhanced, and their color stability greatly improved throughout the entire storage period, thus contributing significantly as long-lived orange-red pigments to the maintenance of aged wine color.